Immune checkpoint inhibitor therapy-induced hypophysitis ∼ a case series of Taiwanese patients - Lin, Chia-Hung; Chen, Kuan-Hua; Chen, Kuan-Yu; Shih, Shyang-Rong; Lu, Jin-Ying (Journal of the Formosan Medical Association, 2019)
Immune checkpoint blockade-based immunotherapy is a new modality of cancer treatment with a unique mechanism that has gained increased numbers of indication and is now used in several cancer types. However, immune-related adverse events (irAEs) emerge as a new entity of diseases involving one or multiple organ systems. irAEs could result in interruption of immunotherapy, morbidities or even death. Among various manifestations of irAEs, immune-mediated hypophysitis is rare but important, requiring prompt diagnosis and treatment to avoid life-threatening conditions. We report seven cases of immune-mediated hypophysitis in Taiwan. They suffered from various types of advanced cancer and received different regimens of immune checkpoint inhibitors. The time of onset after initiation of immunotherapy ranged from 5 to 36 weeks. All seven subjects were diagnosed of central adrenal insufficiency, while four of them had primary hypothyroidism. There was no typical finding of infiltrative hypophysitis on the pituitary MRI. There was no documented hormone recovery after diagnosis of hypophysitis, and the tumor responses to immunotherapy were variable in these seven patients. In conclusion, immune-mediated hypophysitis is often irreversible. Fortunately, it can be managed adequately with hormone replacements. Further investigations are warranted to unveil underlying mechanisms and ethnic differences to guide the solutions.